Exploring the potential of using undergraduates' knowledge, skills and experience in research methods as a proxy for capturing learning gain. Issue 1 (1st January 2018) - Turner, Rebecca; Sutton, Carole; Muneer, Reema; Gray, Claire; Schaefer, Nadine; Swain, Julie
Abstract: Learning gain is a politicised concept within contemporary HE, and as such has been aligned with agendas of teaching excellence and learning outcomes but the extent to which it captures actual learning has yet to be clarified. Here, we report the outcomes of a learning gain study which examines how students' knowledge, skills and experiences as researchers develops throughout their studies. We examine data from a self-reporting survey administered across a university and college-based HE providers during students' second year of undergraduate study. The data highlight disciplinary differences in student engagement with research methods and the significance of perceived relevance of research methods to students' learning. These findings do have a bearing on the development of measures of learning gain as they are demonstrating the complexity of capturing student learning across disciplines. Our findings can be employed to develop a method of capturing learning gain that can be integrated into undergraduates' research methods education.